In-situ mapping of local orientation and strain in a fully operable infrared sensor. (November 2021) - Yildirim, C.; Brellier, D.; Pesci, R.; Boulard, F.; Baier, N.; Zhou, T.; Nguyen-Thanh, T.; Gergaud, P.; Schulli, T.; Ballet, P.
Graphical abstract: Abstract: Hybridized focal plane array (FPA) HgCdTe (MCT) sensors are the workhorse of high performance infrared detectors covering a broad range of applications from space investigation to gas monitoring. Despite the improvements in the performance of these sensors in the last decades, device failure due to the lattice and thermal expansion mismatches between MCT and the Si readout circuit still affects the overall MCT detector performance. In this work, we use in-situ dark-field X-ray microscopy (DFXM) to map the structural variations of a fully operable MCT sensor at temperatures down to 80 K. We report, for the first time, on the nanoscale structural evolution over a large population of photodiodes at operating temperatures with high spatial and angular resolution. Our results show that lattice distortion and strain in the MCT epilayer increases at lower temperatures. The FWHM values of the rocking curves reach up to 0.02 ∘ at 80 K, three times higher than the room temperature value. The thermal cycle results show that the thermal effects are almost completely reversible and the measured strain is in the elastic regime. We discuss the origin of the temperature-generated structural modifications using complementary finite element modelling.